Overall Survival of Patients With Unresectable or Metastatic BRAF V600-Mutant Acral/Cutaneous Melanoma Administered Dabrafenib Plus Trametinib: Long-Term Follow-Up of a Multicenter, Single-Arm Phase IIa Trial - Mao, Lili; Ding, Ya; Bai, Xue; Sheng, Xinan; Dai, Jie; Chi, Zhihong; Cui, Chuanliang; Kong, Yan; Fan, Yun; Xu, Yanjun; Wang, Xuan; Tang, Bixia; et al. (Frontiers in Oncology, 2021)
Objectives: To examine the long-term survival outcome of dabrafenib in combination with trametinib in Chinese patients with unresectable or metastatic acral/cutaneous melanoma with BRAF-V600 mutation and to explore potential predictors of effectiveness. Methods: This was a long-term follow-up of Chinese patients with unresectable or metastatic BRAF V600-mutant acral/cutaneous melanoma administered dabrafenib (150 mg twice daily) plus trametinib (2 mg once daily) in an open-label, multicenter, single-arm, phase IIa study (NCT02083354). Efficacy endpoints included objective response rate (ORR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS). The impacts of baseline characteristics on PFS and OS were analyzed. Results: A total of sixty patients were included. The median age was 48 years, and 24 patients (40.0%) were male. Totally 12 individuals (20.0%) had acral melanoma, and 45 (75.0%) had failed previous systemic therapy. Up to July 2020, the median duration of follow-up was 37.0 (95% confidence interval [CI] 29.1-44.9) months. The updated ORR was 71.7% (95%CI 60.3%-83.1%). The 3-year OS rate was 28.8% (95%CI 19.1-43.6%) in the overall population, and 35.7% (95%CI 15.5–82.4%) in acral melanoma patients. The median DOR was 7.5 months (95%CI 4.5 to 10.5). Baseline normal lactic dehydrogenase (LDH), metastatic organ sites ＜3 and complete response to combination therapy with dabrafenib plus trametinib were associated with improved PFS and OS. Conclusion: Dabrafenib combined with trametinib confer long-term survival in Chinese patients with BRAF V600-mutant, unresectable or metastatic acral/cutaneous melanoma.